Compressive and tensile properties of polyurethane foam mimicking trabecular tissue in artificial femoral head bones - Zerdzicki, Krzysztof; Znaczko, Aleksander; Kondrusik, Aleksandra; Korbut, Wiktoria (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionMost orthopedic implants for fracture fixation and joint replacement are commonly tested on artificial bones. Polyurethane foam is one of the most frequently used synthetic bone materials for mimicking human trabecular tissue. The study aimed to examine the compressive and tensile behavior of polyurethane foams mimicking trabecular tissue in artificial human femurs and assess their potential to replicate the osteoporotic type of human bone tissue.Materials and methodsTwo types of SYNBONE femur models, one of normal density (model 2350) and one of lower density (model LD2350), and three types of Sawbones femur models (models 1130-21-8, 1130-21-3, and 1130-192) were investigated. Polyurethane foams were extracted as slices cut in the coronal plane from the femoral head. Cuboid samples were cut in three directions and uniaxial tested to identify compressive and tensile properties, including elastic modulus, Poisson’s ratio, yield limit, and ultimate strength.ResultsThe ANOVA test revealed that only SYNBONE LD2350 trabecular tissue exhibits anisotropy properties (p < 0.001). In most cases, the tensile properties were greater than compressive ones (t-test, p < 0.001).ConclusionThe obtained results are within the ranges suggested by other authors for mimicking osteoporotic human tissue. The presented data broadens the range of data on mechanical properties provided by the producers. These data can serve as a reference for research using composite femurs made of these particular polyurethane foams for conducting biomechanical studies and validating accompanying numerical simulations.